The acceptance of farmers on the MyGAP system in paddy cultivation at Tangkak Johor / Nurul Hidayah Md Suhaimi - Md Suhaimi, Nurul Hidayah (Faculty of Plantation and Agrotechnology, 2018)
The Malaysian paddy and rice industry has always been given special treatment based on the strategic importance. The government of Malaysia introduced Malaysian certification scheme for Good Agricultural Practices (MyGAP) as one of the strategy to enhancing quality, safety and environmental-friendly product and also to fulfill the preference and demand of consumers. The purpose of this study was to determine the relationship between several variables contributing to acceptance of farmers towards MyGAP system and to identify which variables namely level of knowledge, proper farm management and environment management can be used to predict the acceptance factors of farmers towards MyGAP implementation system in Tangkak, Johor. Researchers get a sample of 195 respondents, and examine whether such variables became the factors that contribute to the acceptance for this topic. The study was conducted using questionnaires that were distributed to the respondents and the results analyzed using reliability test and correlation analysis using the SPSS and Eviews. From the analysis, the researchers found that only one variable which is proper farm management has strong correlation and influenced acceptance of farmers toward MyGAP implementation system in paddy cultivations. Other factors have relationship with acceptance farmers but not influenced them because most of the farmers wished for better farm gate price rather than practicing safety assurance and need much support from the relevant agriculture agencies. Thus, the distribution of knowledge and enforcement related to food safety assurance should be exaggerated in order to improve the implementation process of sustainable paddy farming practices.